REFORMS AND PROSPECTS FOR THE DEVELOPMENT OF THE PARTICIPATORY BUDGETING INITIATIVE IN UZBEKISTAN - Khamidov Khabibullo Hikmatulla o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article highlights the ongoing work on improving the standard of living the population and solving socio-economic problems and shortcomings facing citizens, the active participation of citizens in the rational use of funds allocated from the state budget to improve local infrastructure and solving problems that have become a systemic issue, funds allocated within local budgets and state programs in the most demanded areas for the population, the implementation of a voting system on relevant proposals.